A TRAINING IN MAKING LIQUID SOAP FROM DURIAN SKIN (Durio zibenthinus Murr) FOR THE PKK GROUP OF RINDU HATI HEART VILLAGE - Versita, Riana (Journal of Community Service, 2023)
One of the problems that we often encounter is durian skin waste (Durio zibethinus Murr.). To overcome this problem, innovation is needed in managing durian skin waste. One way of using durian skin is by making cosmetic preparations that can be used as commodities for MSMEs, such as liquid soap, where durian skin extract has useful ingredients such as flavonoids as antibacterials and antioxidants that can brighten the skin and rejuvenate the skin. The method of this service activity is a participatory community empowerment method with the participatory rural appraisal (PRA) model, namely a method that emphasizes community involvement in all activities carried out. The activity was carried out on July 10, 2023, at 09.000 s.d. The completion of community service activities regarding training on making liquid soap from durian skin waste (Durio zibenthinus Murr) for the PKK group in Rindu Hati Village was carried out well and received a very good response from the participants.